Advances in advertising research (Vol. IV) : The changing roles of advertising - Dahlen, Micael; Okazaki, Shintaro; Rosengren, Sara (EAA Series,, 2013)
Advances in Advertising Research are published by the European Advertising Academy (EAA). This volume is a compilation of research presented at the 11th International Conference in Advertising (ICORIA), which was held in Stockholm (Sweden) in June 2012. The conference gathered 150 leading researchers from 22 countries under the conference theme "The changing roles of advertising". The book provides international state-of-the-art research with 30 articles by renowned scholars from the worldwide ICORIA network.   Contents ·         The Roles of Advertising ·         The Faces of Advertising ·         Perceptions of Advertising ·         Reception of Advertising   Target Groups ·         Researchers, students, and practitioners in the fields of advertising, communications, marketing, and media management   The Editors: Sara Rosengren and Micael Dahlén work at the Stockholm School of Economics. Shintaro Okazaki is Associate Professor of Marketing at the College of Economics and Business Administration, Universidad Autónoma de Madrid, Spain.